Cell Therapy in Patients with Critical Limb Ischemia - Rita Compagna; Bruno Amato; Salvatore Massa; Maurizio Amato; Raffaele Grande; Lucia Butrico; Stefano de Franciscis; Raffaele Serra (Hindawi Limited, 2015)
Critical limb ischemia (CLI) represents the most advanced stage of peripheral arterial obstructive disease (PAOD) with a severe obstruction of the arteries which markedly reduces blood flow to the extremities and has progressed to the point of severe rest pain and/or even tissue loss. Recent therapeutic strategies have focused on restoring this balance in favor of tissue survival using exogenous molecular and cellular agents to promote regeneration of the vasculature. These are based on stimulation of angiogenesis by extracellular and cellular components. This review article carries out a systematic analysis of the most recent scientific literature on the application of stem cells in patients with CLI. The results obtained from the detailed analysis of the recent literature data have confirmed the beneficial role of cell therapy in reducing the rate of major amputations in patients with CLI and improving their quality of life.